Association of the TNFa13 microsatellite with systemic sclerosis in Japanese patients. Issue 4 (1st April 2000) - Takeuchi, Fujio; Nabeta, Hiromi; Füssel, Monika; Conrad, Karsten; Frank, Karl-Heinz
Abstract : OBJECTIVES: To elucidate the contribution of microsatellite polymorphisms of TNFa and TNFb alleles to the pathogenesis of systemic sclerosis (SSc) by comparing the allele distribution among populations with different HLA susceptibility genes in SSc. METHODS: TNFa and TNFb microsatellite polymorphisms were determined by PCR in 54 Japanese and 50 German SSc patients and in normal controls. HLA-DR genotyping was carried out by PCR-SSCP. RESULTS: The frequency of TNFa13 was significantly increased in Japanese SSc (p=0.011, OR=8.53, 95% confidence intervals (95%CI)=2.46, 32.51, and p<1.0 × 10E-5, OR=10.35, 95%CI=4.88, 22.09) and SSc with antitopoisomerase I antibody (a-Scl-70) (p=0.021, OR=33.25, 95%CI=3.39, 800.76, and p<1.0 × 10E-5, OR=24.42, 95%CI=8.40, 72.83), compared with the German patient group and German controls, respectively. This increase was not only attributable to a higher prevalence of TNFa13 in Japanese compared with Germans (p=0.005, OR=3.55, 95%CI=1.60, 7.85) but was also caused by an increase in SSc, especially in the a-Scl-70 positive patients (p=0.028, OR=6.88, 95%CI=1.16, 22.60) compared with Japanese controls. TNFa13 was positively in linkage disequilibrium with HLA-DRB1*1502 (LD=0.053, t =2.69). Association analysis indicated that both TNFa13 and DRB1*1502 might have comparable probabilities of being susceptibility factors for SSc with a-Scl-70 in Japanese. Prevalences of TNFa6 and 13 were significantly increased and prevalences of TNFa2, and 7 were significantly decreased in Japanese controls as compared with German controls. CONCLUSION: TNFa13 is a genetic marker for SSc with a-Scl-70 in Japanese patients. Various differences in the prevalences of TNFa alleles between Japanese and German controls were established.